Relations between mandible-only advancement surgery, the extent of the posterior airway space, and the position of the hyoid bone in Class II patients: a three-dimensional analysis. Issue 10 (December 2019) - Rückschloß, T.; Ristow, O.; Berger, M.; Engel, M.; Freudlsperger, C.; Hoffmann, J.; Seeberger, R.
Abstract: The objective of the present study was to evaluate the relation between mandibular advancement, the three-dimensional extent of the posterior airway space (PAS), and the position of the hyoid bone, using cone-beam computed tomography (CT). Twenty-eight Class II patients (21 women (mean (SD) age 29 (9) years) and seven men (mean (SD) age 23 (6) years)), who had had mandibular-only advancement surgery (Obwegeser-Dal Pont) were included in the study. In each case, cone-beam CT scans were taken one week before and six months after operation, and a retrospective analysis made of the alterations of several airway variables (volume, mean cross-sectional area, and diameter) and the three-dimensional extent of mandibular and hyoid movement, by using IPlan® cranial software. A linear regression was also done to correlate mandibular advancement, the movement of the hyoid bone, and airway variables. There were significant postoperative increases in all volumetric PAS variables, and in most diametric and spherical variables (p < 0.05). There was also a significant linear relation between forward displacement of the mandible and the movement of the hyoid bone (p < 0.05). These results show that mandible-only advancement surgery causes an increase in most dimensions of the PAS. This intervention can be assumed to reduce airway resistance and therefore might be a suitable treatment option for patients with obstructive sleep apnoea syndrome.